Evaluation of prokinetic agents used in the treatment of gastroparesis. (1st January 2017) - Roe, Neil A; Sakaan, Sami; Swanson, Heather; Twilla, Jennifer D
Abstract: Background/Aim: Hospitalizations due to gastroparesis have increased in the last 20 years with limited advancements in pharmacologic therapy. Although therapy primarily consists of prokinetic agents, little is known about their effects on hospital outcomes. The aim of our study was to determine whether common prokinetic therapies (metoclopramide and erythromycin) improve outcomes in gastroparesis patients. Methods: A retrospective review of adult patients admitted with a primary diagnosis of gastroparesis between 7 January 2011 and 7 January 2014 was conducted. Patients were divided into two groups based on whether they received prokinetic therapy (PRO) during hospitalization or not (NO). Groups were compared to determine length of stay (LOS), 30-day readmission rates, and risk factors affecting these outcomes. Results: Of the 82 patients included in our study, 57 received prokinetic therapy. Mean length of stay (LOS) was 5.8 ± 4.2 days, with a significantly shorter LOS in the NO group (3.7 ± 1.9 vs. 6.7 ± 4.5; p  = 0.002). Among patients studied, 30.5% were readmitted within 30 days from discharge with no significant reduction in the PRO group (35.1% PRO vs. 20% NO; p  =0.23). Patients with idiopathic gastroparesis had significantly longer LOS (6.9 ± 4.6 vs. 4.2 ± 2.8; p  = 0.003). In the PRO group, those who received intravenous (IV) therapy had a significantly shorter LOS (4.9 ± 2.5 IV vs. 8.0 ± 5.3 oral; p  = 0.01). Conclusions: Treatment of gastroparesis patients with prokinetic agents did not shorten the LOS nor decrease 30-day readmission rates. In those receiving prokinetics, the IV route was associated with reduced LOS.